Research trends and frontiers in exercise for movement disorders: A bibliometric analysis of global research from 2010 to 2021 - Ji-Wei Chen; Yue Guan; Yi-Li Zheng; Kun Zhu (Frontiers in Aging Neuroscience, 2022)
ObjectiveTo conduct a bibliometric analysis of trends and frontiers on exercise-based non-pharmacological treatments for movement disorders published between 2010 and 2021.MethodsThe Web of Science (WOS) Core Collection database was searched for articles published between 2010 and 2021. The CiteSpace software was used for in-depth analysis of the countries, institutions, journals, and collaboration networks among authors and their types of articles, developmental directions, references, and hot keywords of published articles.ResultsA total of 2,626 published articles were retrieved by search formula and included in the analysis. The number of publications fluctuated during this period, with 96 countries, 3,058 institutions, and 886 academic journals having published articles in this area, with subject classifications that focused on Clinical Neurology and Neurosciences. The United States has maintained its dominant and most influential position in exercise-based non-pharmacological research on movement disorders. Among research institutions and journals, the League of European Research Universities and Movement Disorders journals published the highest number of academic articles. In the last five years, the hot research topics by burst keyword analysis, are focused on treatments, research advances, and clinical treatments.ConclusionResearch on exercise-based non-pharmacological treatments for movement disorders is generally on the rise from 2010 to 2021. The bibliometric analysis of this area will help provide potential collaborations among researchers, frontiers, and directions for development.